A gestão escolar democrática como espaço-tempo de formação de professores alfabetizadores - Braga, Vanessa Auer (2024)
This work, entitled “Democratic school management as a space-time for training literacy teachers”, had the general objective: to understand the historical processes that corroborate the non-appropriation of children's reading and writing. The specific objectives are: a) organize and develop collective processes and dialogues for training literacy teachers at school; b) analyze the historical and social conditions of the exposed problem, through dialogues and collective listening; c) reflect, collectively, on the categories emerging from the analysis of data obtained through listening to the subjects involved and discuss intervention proposals; d) elaborate, based on the synthesis of the phenomenon under study, proposing intervention in the scope of management and training of literacy teachers, with a view to focusing on new possibilities for pedagogical organizations in literacy. This research had as its theoretical contribution the concepts of Bakhtin and his Circle (2003, 2017); Caldart (2023), Curado (2018), Freitas (2018), Gontijo (2003, 2008, 2014), Vazquez (2007), among others. Methodologically, this dissertation is of a participatory qualitative nature, as it understands that qualitative research helps to understand and value narratives, expressions of thoughts, voices, writings, images, silences, among other manifestations. To produce data, it uses dialogue circles, recordings and analysis of documents. As a result, it understands the student as a citizen practicing the exercise of his citizenship through writing, recognized as a space for these exercises and also for resistance. The social function of writing is an ethical and political act, in which the subject takes responsibility for what he writes and, at the same time, demands a response, therefore the result of this research is not limited to what was presented here, because it is a process dialectic with no date to end. The epistemology used in this study has produced and will produce other and new epistemologies, a path that mobilizes transformations